Credit scoring development in the light of the new Brazilian General Data Protection Law - Oliveira-Junior, Robinson A. A. de (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe); 2021: Anais do IX Symposium on Knowledge Discovery, Mining and LearningDO - 10.5753/kdmile.2021.17462, 2021)
With the advent of the new Brazilian General Data Protection Law (LGPD) which determines the right to the explanation of automated decisions, the use of non-interpretable models for human beings, known as black boxes, for the purposes of credit risk assessment may remain unfeasible. Thus, three different methods commonly applied to credit scoring – logistic regression, decision tree, and support vector machine (SVM) – were adjusted to an anonymized sample of a consumer credit portfolio from a credit union. Their results were compared and the adequacy of the explanation achieved for each classifier was assessed. Particularly for the SVM, which generated a black box model, a local interpretation method – the SHapley Additive exPlanation (SHAP) – was incorporated, enabling this machine learning classifier to fulfill the requirements imposed by the new LGPD, in equivalence to the inherent comprehensibility of the white box models.